2021
DOI: 10.1002/cey2.156
|View full text |Cite
|
Sign up to set email alerts
|

Self‐catalyzed formation of strongly interconnected multiphase molybdenum‐based composites for efficient hydrogen evolution

Abstract: Molybdenum carbide (MoxC) with variable phase structure possesses flexible hydrogen‐binding energy (HBE), which is a promising hydrogen evolution reaction (HER) catalyst. Herein, a hybrid multiphase MoxC freestanding film coupled with Co3Mo (CM/MoxC@NC) is synthesized through the electrospinning method supplemented by the heteroatom incorporation. CM/MoxC@NC surpasses its pure phase counterparts and exhibits remarkable catalytic activity at 114 mV to deliver a current density of 10 mA cm−2 in acid, which is am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…18,22,23 However, ΔG H* alone is hardly sufficient to describe the activity of HER in alkaline solutions 26 27,28 In this case, considering the relatively highenergy barrier for water dissociation of Ru, 26 a well-designed substrate with good water dissociation ability is essential to achieving efficient electrocatalysis for alkaline HER. Previous work has confirmed that Mo 2 C possesses a low water dissociation energy in alkali, 29,30 and thus a carbon-Mo 2 C composite support may be a good choice for Ru anchoring.…”
Section: Introductionmentioning
confidence: 92%
“…18,22,23 However, ΔG H* alone is hardly sufficient to describe the activity of HER in alkaline solutions 26 27,28 In this case, considering the relatively highenergy barrier for water dissociation of Ru, 26 a well-designed substrate with good water dissociation ability is essential to achieving efficient electrocatalysis for alkaline HER. Previous work has confirmed that Mo 2 C possesses a low water dissociation energy in alkali, 29,30 and thus a carbon-Mo 2 C composite support may be a good choice for Ru anchoring.…”
Section: Introductionmentioning
confidence: 92%
“…[1][2][3][4][5] Electrocatalytic water splitting via the hydrogen evolution reaction (HER) is a viable high-purity hydrogen generation technology with widely accessible reactants, competitive cost-effectiveness, and stable output that aroused intense research in contrast to the traditional natural gas decomposition and watergas conversion. [6][7][8][9][10] Platinum (Pt)-based materials are remaining utilized as the most desirable HER catalysts but are largely limited by the prohibitive costs and scarce reserves. [11][12][13][14][15][16] Palladium (Pd) with a similar electronic structure to Pt has been a promising Pt-free alternative with a much richer reservation.…”
Section: Research Articlementioning
confidence: 99%
“…Urea electrooxidation received great attention among the above organics due to its advantages as non-toxic, rich source, and thermodynamic feasibility at low potential. [18][19][20][21][22] However, the complex sixelectron reaction of UOR inherently has sluggish kinetics, 23 which require catalysts to accelerate the reaction rate. 24 Nibased catalysts [24][25][26][27][28] have been widely reported in UOR because Ni metal sites can efficiently decompose urea into NH 3 and CO 2 .…”
Section: Introductionmentioning
confidence: 99%